Hubungan Pola Makan Dan Pola Menstruasi Dengan Kejadian Anemia Remaja Putri Di Wilayah Kerja Uptd Puskesmas Telang Siong Tahun 2025 - Melda Hayati Rahmi; Tri Tunggal; Efi Kristiana; Hapisah (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
Background: Telang Siong Health Center is ranked first for female adolescents with anemia 55.74, there are 235 adolescents and 131 teenagers suffering from anemia. Objective: To determine the relationship between dietary patterns and menstrual patterns with the incidence of anemia in the work area of the Telang Siong Community Health Center. Method: Analytical research with cross-sectional design. The number of female adolescents in the Telang Siong Community Health Center (UPTD) in 2025 was 235 people. Sampling was done using purposive sampling technique. The research instrument was a questionnaire and HB examination sheet, and the analysis was carried out using the Chi-Square test. Results: The results of the characteristics of age, class and place of residence affect the eating patterns of adolescents. There is a relationship between eating patterns and the incidence of anemia in adolescent girls with a p value of 0.000. There is a relationship between menstrual patterns and the incidence of anemia in adolescent girls with a p value of 0.001. There is a relationship between the menstrual cycle and the incidence of anemia in adolescent girls with a p value of 0.000. Conclusion: Adolescent girls with unhealthy diets, inadequate nutrient intake, especially iron, and a habit of consuming fast food tend to have a higher risk of anemia. Furthermore, irregular menstrual patterns, with longer periods and heavier blood loss, also contribute to an increased risk of anemia. Adopting a healthy diet and regularly monitoring menstrual patterns are crucial for preventing anemia in adolescent girls. Latar Belakang: Puskesmas Telang Siong berada diurutan pertama remaja putri dengan anemia 55,74, terdapat 235 remaja dan 131 remaja yang menderita anemia. Tujuan: mengetahui hubungan pola makan dan pola menstruasi dengan kejadian anemia di wilayah kerja UPTD Puskesmas Telang Siong. Metode: Penelitian analitik dengan desain cross sectional. Jumlah remaja putri UPTD Puskesmas Telang Siong pada tahun 2025 sebanyak 235 orang., pengambilan sampel menggunakan teknik purposive sampling. Dengan Instrumen penelitian kuesioner dan lembar pemeriksaan HB, selanjutnya analisis menggunakan uji Chi-Square. Hasil: Hasil karakteristik umur, kelas dan tempat tinggal mempengaruhi pola makan remaja, Ada hubungan antara  pola makan dengan kejadian anemia pada remaja putri  dengan hasil  p value sebesar 0,000,Ada hubungan antara Pola menstruasi dengan kejadian anemia pada remaja putri dengan hasil  p value sebesar 0,001,Ada hubungan antara siklus menstruasi dengan kejadian anemia pada remaja putri dengan hasil  p value sebesar 0,000. Kesimpulan: Remaja putri dengan pola makan yang tidak sehat, asupan zat gizi terutama zat besi yang tidak mencukupi, serta kebiasaan konsumsi makanan yang instan cenderung memiliki risiko anemia lebih tinggi. Selain itu, pola menstruasi yang tidak teratur, dengan lama menstruasi yang lebih panjang dan jumlah darah yang keluar lebih banyak, juga berkontribusi terhadap meningkatnya risiko anemia. Pentingnya penerapan pola makan sehat dan pemantauan pola menstruasi secara rutin sebagai upaya pencegahan anemia pada remaja putri. Kata Kunci: Pola Makan, Pola Menstruasi, Kejadian Anemia Remaja